B-group vitamins - Leblanc, Jean Guy Joseph (2018)
Vitamins are organic micronutrients which are substances that must be present in small quantities and that are essential for the growth and development of the human body and are required in numerous metabolic reactions to maintain homeostasis. The 13 vitamins that are required by human metabolisms are divided as being either fat-soluble (such as vitamins A (retinols and carotenoids), D (cholecalciferol), E (tocopherols and tocotrienols), and K (quinones)), or water soluble (that include vitamin C (ascorbic acid) and the B group vitamins). In the latter group (B-group) these include: vitamin B1 (thiamine), vitamin B2 (riboflavin), vitamin B3 (niacin), vitamin B5 (pantothenic acid), vitamin B6 (pyridoxine), vitamin B7 (biotin), vitamin B9 (folic acid or folate) and vitamin B12 (cobalamins).